Measurement Of Customer Satisfaction Using Fuzzy Service Quality Method At PT.ABC - Helmi Kurniawan (Journal of Intelligent Decision Support System (IDSS), 2023)
Customer satisfaction is obtained by someone when they feel satisfied or dissatisfied based on a comparison of product or service performance with their expectations. This factor is very crucial in assessing whether an industry, especially the service industry, is successful or not. The quality of customer satisfaction can be assessed through the difference between customer expectations and perceptions. PT. ABC effectively provides information to customers about the evaluation of the quality of services provided by its employees, as well as the factors that have an influence on the level of customer satisfaction in using these services. This study aims to measure and evaluate the quality of service with the Service Quality method, namely comparing customer expectations and perceptions. For this reason, Service Quality consists of five main dimensions, namely tangibles (physical factors), reliability (reliability), responsiveness (responsiveness), assurance (certainty), and empathy (empathy). The results showed that the service quality of PT.ABC is close to 7. This proves that PT.ABC must improve the quality of its services so that customers feel very satisfied. The highest factor is the factor that most influences customer satisfaction and has the highest gap, which is the assurance factor.